ASAS HUKUM DALAM UNDANG-UNDANG NOMOR 39 TAHUN 2004 UNTUK MEWUJUDKAN PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA YANG BERMARTABAT - Husni, Lalu (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2010)
Legal principles (rechtsbeginselen) in Act No. 39, 2004 have not been fully translated as fundamentals in the establishment of legal norms (rechtsnormen) of placement and protection of Indonesian Migrant Workers. The principles which have been translated are the principle of equal rights, the principle of social justice, the principle of equity and justice of gender, and the principle of human trafficking/trafficking in person. The principle that has not been completely translated is the principle of integration. While, the principles which translations could not be found separately are the principle of democracy and the principle of non-discrimination. In order to protect the Indonesian Migrant Workers as dignified human beings, the legal principles should be reviewed again by adding new principles, that is, principle of humanity and principle of state responsibility as the philosophical foundation of the placement and protection of migrant workers in the future.Keywords: Legal principles, The Placement and Protection of Dignified Indonesian Migrant Workers.